The association between sedentary behavior and falls in older adults: A systematic review and meta-analysis - YueShuai Jiang; Mei Wang; Shuang Liu; Xiao Ya; GuanTing Duan; ZiPu Wang (Frontiers Media S.A., 2022)
BackgroundIt is generally believed that sedentary behavior (SB) increases the risk of falls among older adults, but the evidence for it remains inconsistent and scarce.PurposeOur study aims to provide a systematic review and meta-analysis of available evidence regarding the association of SB with falls in older adults.MethodA comprehensive search strategy was conducted using several online databases from 1906 to March 2022. Cohort studies both concerning the association between SB and falls and involving participants over 60 years old were regarded as eligible for inclusion. Evidence was pooled by a random-effects meta-analysis. Quality assessment for individual studies was performed with the Newcastle-Ottawa Scale (NOS).ResultsAltogether seven publications were identified, and the age of the 24,750 individuals involved ranging from 60 to 99 years old. Overall quality of the included studies was rated as moderate-to-high quality. We found that SB was significantly associated with increased risk of falls compared with non-SB among older adults [Odds ratio (OR) = 1.17, 95% confidence interval (CI): 1.07-1.28; I2 = 46.90%, Pheterogeneity = 0.07, random model]. Subgroup analyses that stratified the studies according to NOS score showed significant differences between groups. Subgroup analysis stratified by SB measurement, sample size, region, publication year, and follow-up duration showed no significant differences between groups.ConclusionThe findings provide reliable support for the hypothesis that sedentary lifestyles are strong predictors of falls among older adults, offering critical indications to develop strategies for fall prevention.